Menggali Kemampuan Guru dalam Mengembangkan Instrumen Evaluasi Pembelajaran IPS Berbasis HOTS dengan Pedekatan TPACK: Exploring Teachers' Ability to Develop HOTS-Based Learning Evaluation Instruments for Social Studies Using the TPACK Approach - Abu, Ardillah; Suharto; Hasriani; R Batalipu, Emi (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2024)
This research aims to explore teachers' abilities in developing evaluation instruments for social studies learning based on Higher Order Thinking Skills (HOTS) using a Technological Pedagogical Content Knowledge (TPACK) approach at MTsN 1 Palu. The research method employed is descriptive qualitative. Data were collected through observation, interviews, and document analysis related to the development of evaluation instruments for social studies. The research results indicate that teachers at MTsN 1 Palu have demonstrated strong abilities in developing HOTS-based evaluation instruments with the TPACK approach. Students effectively integrate technological knowledge, pedagogical knowledge, and content knowledge in the development process of social studies evaluation instruments that promote higher-level thinking skills. Furthermore, teachers exhibit a solid understanding of the TPACK concept, which aids them in designing relevant and effective evaluation instruments. This research provides valuable insights into the pivotal role of TPACK in the development of HOTS-based evaluation instruments in the context of social studies education at MTsN 1 Palu.